TRANSFORMATION MULTICULTURAL EDUCATION - Amang Fathurrohman, Muhammad Nur Hadi (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan)
Multicultural education is not just to teach about the different cultures of the various ethnic and religious groups but also supports the appreciation, comfort, to tolerance of other cultures. As a transformational process, present multicultural education as a process through all aspects of education are tested and criticized and rebuilt on the basis of the ideals of equality and social justice. In such conditions more appropriately directed multicultural education as an advocate for creating a tolerant and free society of tolerance.